2009
DOI: 10.1186/1744-8069-5-66
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin-Induced Loss of Phosphorylated Heavy Neurofilament Subunit Neuronal Immunoreactivity in Rat Drg Tissue

Abstract: BackgroundOxaliplatin and related chemotherapeutic drugs cause painful chronic peripheral neuropathies in cancer patients. We investigated changes in neuronal size profiles and neurofilament immunoreactivity in L5 dorsal root ganglion (DRG) tissue of adult female Wistar rats after multiple-dose treatment with oxaliplatin, cisplatin, carboplatin or paclitaxel.ResultsAfter treatment with oxaliplatin, phosphorylated neurofilament heavy subunit (pNF-H) immunoreactivity was reduced in neuronal cell bodies, but unch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
7
16
0
Order By: Relevance
“…Following the finding that oxaliplatin induced a decrease in NCV and action potential amplitude; we examined the morphology of DRG neurons and sciatic nerve at the light and electron microscope levels. Our findings that the diameter of DRG cell bodies is reduced after chronic oxaliplatin treatment is also similar to findings in the rat [7,34,43,45,46], which are suggestive of neuronal atrophy that could be related to a decrease in phosphorylated neurofilament [45]. Finally, our morphological examination of DRGs and sciatic nerves revealed that many of the neurons were multinucleolated, that the nucleoli were eccentric and that rare nerve fibers presented mild signs of axonopathy.…”
Section: Discussionsupporting
confidence: 90%
“…Following the finding that oxaliplatin induced a decrease in NCV and action potential amplitude; we examined the morphology of DRG neurons and sciatic nerve at the light and electron microscope levels. Our findings that the diameter of DRG cell bodies is reduced after chronic oxaliplatin treatment is also similar to findings in the rat [7,34,43,45,46], which are suggestive of neuronal atrophy that could be related to a decrease in phosphorylated neurofilament [45]. Finally, our morphological examination of DRGs and sciatic nerves revealed that many of the neurons were multinucleolated, that the nucleoli were eccentric and that rare nerve fibers presented mild signs of axonopathy.…”
Section: Discussionsupporting
confidence: 90%
“…Increasing evidence indicates that the cytoskeleton is one of the most important targets of neurotoxic agents. Many studies have shown that changes occur in Nf proteins during development in response to neurotoxicity in vivo [19] and neurotoxic agents were correlated with decreased neurite growth in vitro [20] . Previous studies have demonstrated a specific pattern of loss of pNfH immunoreactivity in rat DRG and nerve tissue after oxaliplatin administration [21] .…”
Section: Discussionmentioning
confidence: 99%
“…According to their size, cells were classified as: small (cross-sectional area £500 mm 2 ), medium (500-1000 mm 2 ), large (1000-1500 mm2), and very large (>1500 mm 2 ) [14,15].…”
Section: Image Analysis Of Drg Neurons: Morphometry and Quantificatiomentioning
confidence: 99%